The Dow Jones-Irwin guide to financial modeling - Morris, James R. (Homewood, Ill. : Dow Jones-Irwin, 1987)
Explains the goals of financial planning, shows how to develop a model, and discusses simulation, forecasting, uncertainty, and risk
Includes bibliographical references and index.
oif 25/07/16
Loans
Keywords: Business enterprises; Corporations